2022
DOI: 10.1038/s41598-022-05499-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endometriosis on immunity and mucosal microbial community dynamics in female olive baboons

Abstract: Endometriosis is defined as the growth of endometrial tissue in ectopic locations, and is associated with altered immune and microbial phenotypes. It is unclear if these changes are the result of the disease or may be causative. We induced endometriosis in non-human primates (Papio Anubis) to test our hypothesis that the growth of endometriotic lesions results in alterations in immune and microbial dynamics that may advance disease progression. Baboon samples were collected pre-inoculation (prior to disease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Le et al detected that microbiome diversity and abundance were altered at each baboon induced of endometriosis. The induction of endometriosis decreased peripheral Tregs cells while Th17 cells increased at all post-induction collections that caused an immune shift toward an inflammatory profile and altered mucosal microbial profiles ( Le et al, 2022 ). More and more evidences suggest that the abnormal quantity and activity of Treg cells can lead to dysregulation of the immune microenvironment in the body, decreased pelvic immune function, and immune escape, thereby promoting the implantation and growth of ectopic endometrium outside the uterus.…”
Section: The Possible Mechanism Of Gut Microbiota Involved In the End...mentioning
confidence: 99%
“…Le et al detected that microbiome diversity and abundance were altered at each baboon induced of endometriosis. The induction of endometriosis decreased peripheral Tregs cells while Th17 cells increased at all post-induction collections that caused an immune shift toward an inflammatory profile and altered mucosal microbial profiles ( Le et al, 2022 ). More and more evidences suggest that the abnormal quantity and activity of Treg cells can lead to dysregulation of the immune microenvironment in the body, decreased pelvic immune function, and immune escape, thereby promoting the implantation and growth of ectopic endometrium outside the uterus.…”
Section: The Possible Mechanism Of Gut Microbiota Involved In the End...mentioning
confidence: 99%
“…The majority of the clinical studies investigating endometriosis and microbiome changes were derived from Asia including Japan, China, Taiwan, Korea, and Turkey ( Table 3 , Supplementary Table S1 ) [ 21 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. There were also some studies from the United States, Brazil, Sweden, and Canada [ 119 , 120 , 121 , 122 , 123 ]. Almost all the clinical trials conducted diagnosed endometriosis cases via laparoscopy or histology tests and scored based on the criteria described in the Revised American Society for Reproductive Medicine (r-ASRM) classification of endometriosis.…”
Section: The Intricate Relationship Between the Female Reproductive T...mentioning
confidence: 99%
“…Another recent study on non-human primates, olive baboons ( Papio Anubis ) in reproductive age also indicated the involvement of T regulatory cells as they investigated changes in the gastrointestinal and urogenital microbiome [ 121 ]. Similar to findings from the rodents’ model of endometriosis, the team reported dynamic changes in the gut microbiome of these olive baboons throughout their 15-months study.…”
Section: The Intricate Relationship Between the Female Reproductive T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have examined the gut microbiota in relation to the development and treatment of endometriosis [ 164 , 165 ]. Though, Hantschel et al [ 166 , 167 ] did not find significant changes in gut microbiota in endometriotic mice 21 days after inoculation, other studies in baboons [ 168 ] or mice [ 169 ] have found that inoculation with endometriosis significantly changed the abundance and diversity of the gut microbiome after 45–90 days, resulting in dysbiosis. The association between gut microbiota and endometriosis was further elucidated in a study by Chadchan et al, who found that oral antibiotics reduced endometriosis progression in mice [ 170 ].…”
Section: Treatments For Oxidative Stressmentioning
confidence: 99%